2020
DOI: 10.1002/jcla.23663
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between plasma serglycin levels and the diagnosis of diabetic retinopathy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…CD44 expression and the inflammatory response were significantly reduced by SRGN siRNA treatment. Wang et al recently found that SRGN levels were dramatically increased in plasma samples from diabetic retinopathy cases compared with type 2 diabetes mellitus or healthy participants [ 22 ], and a very high percentage of patients with diabetic retinopathy develop AD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD44 expression and the inflammatory response were significantly reduced by SRGN siRNA treatment. Wang et al recently found that SRGN levels were dramatically increased in plasma samples from diabetic retinopathy cases compared with type 2 diabetes mellitus or healthy participants [ 22 ], and a very high percentage of patients with diabetic retinopathy develop AD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serglycin (SRGN) is a hematopoietic cell granule proteoglycan that functions in the formation of mast cell secretory granules, mediates the storage of various compounds in secretory vesicles, and thus plays a role in cell apoptosis mediated by cytotoxic cell particles. SRGN might serve as a promising biomarker with high specificity and sensitivity in diabetic retinopathy diagnosis and progression ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…DM-induced visual impairment brings great psychological stress that seriously affects the quality of life. [4,5] It is reported that DR patients are prone to adverse emotional reactions such as anxiety and depression. [6][7][8] It not only threatens the physical and mental health of DR patients, but also reduces the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment of DM is complex, with a long course and unsatisfactory efficacy. DM-induced visual impairment brings great psychological stress that seriously affects the quality of life [4,5] . It is reported that DR patients are prone to adverse emotional reactions such as anxiety and depression [6–8] .…”
Section: Introductionmentioning
confidence: 99%